2022
DOI: 10.3389/fpubh.2021.809463
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation Is Associated With Excessive Smartphone Use Among Chinese College Students

Abstract: BackgroundSuicidal ideation is the first step and a strong predictor of suicide. College students are at a considerably high risk of suicidal ideation, and smartphones are commonly used in this group. However, the relationship between suicidal ideation and smartphone use among Chinese college students is unclear. The current study aimed to investigate the prevalence of suicidal ideation among Chinese college students and its association with smartphone use and addiction factors.MethodsA total of 439 college st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…College students with depression usually felt hopeless and helpless [7], and adverse childhood experiences (ACEs) were recognized as long-distance risks of depression in adulthood [8,9]; smartphone addiction [10,11] and epidemic [12,13]are also important causes of depression among college students, depression and race of college students [14], gender [15], and professional [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…College students with depression usually felt hopeless and helpless [7], and adverse childhood experiences (ACEs) were recognized as long-distance risks of depression in adulthood [8,9]; smartphone addiction [10,11] and epidemic [12,13]are also important causes of depression among college students, depression and race of college students [14], gender [15], and professional [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the indirect effect, we could find only one previous study that have built on Murphy’s findings, and demonstrated that depressive symptoms partially mediated the path leading from SI to PEs among Chilean high-school adolescents (Nunez et al, 2020 ). As for PSU, research has shown that healthy young individuals who report general feeling of poor health, and more particularly greater SI, are more likely to overuse their smartphones (Huang et al, 2021 ; Kim et al, 2019 ), and be more active on social media than other users (Wang et al, 2019 ). Besides, digital media use has gained increased attention as the current era’s environmental risk factor for PEs in healthy young adults (Fekih-Romdhane, Sassi, et al, 2021 ; Lee et al, 2019 ; McMahon et al, 2021 ; Mittal et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a Chinese study found that people with SI were significantly more active on social media compared to other users (Wang et al, 2019 ). Another Chinese study showed that college students with SI in the past year had 2.6-fold increased risk of PSU, reported more than 5 h of current daily smartphone use, and more severe smartphone addiction symptoms (i.e., inability to control craving) (Huang et al, 2021 ). Similarly, a Korean study revealed that college students exhibiting SI had around 2-fold increased risk of smartphone overuse than their counterparts without SI (Kim et al, 2019 ).…”
Section: Problematic Smartphone Use (Psu) As a Mediator Of The Relati...mentioning
confidence: 99%
“…One theory is that prolonged use of cellphones promotes isolation among young people, leading to suicidal ideation. [36,37] Another theory is that cellphones have reduced isolation and improved mental health among young people during the COVID-19 pandemic. Studies supporting the latter theory include a 2022 survey of Japanese university students revealing that smartphone use reduced the risk of is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint…”
Section: Discussionmentioning
confidence: 99%